Book review: Sedimentary structures (4th ed.), by John Collinson & Nigel Mountney, 2019. Dunedin Academic Press Ltd, Edinburgh, Scotland. xii + 340 pages. Paperback: price €40.00, £35.00, $35.00, ISBN 978-1-78046-062-8. - van Loon, A.J. Tom (Geologos, 2020)
Book review: Sedimentary structures (4th ed.), by John Collinson & Nigel Mountney, 2019. Dunedin Academic Press Ltd, Edinburgh, Scotland. xii + 340 pages. Paperback: price €40.00, £35.00, $35.00, ISBN 978-1-78046-062-8.